Female and Unfree in America: Captivity and Slave Narratives - Bercuci Loredana (Romanian Journal of English Studies, 2020)
This study analyses two seminal American memoirs that depict female captivity: A Narrative of the Captivity and Restoration of Mrs. Mary Rowlandson (1682) by Mary Rowlandson and Harriet Jacobs’ Incidents in the Life of a Slave Girl (1861). My aim is to discuss, using the tools of Critical Race Theory, the intersections of gender and race, focusing on how the two women’s femininity, as well as their individuality, is linked to Christianity and motherhood.